Correlation analysis of serum CCL3, TRACP-5b and Sclerostin with the prognosis of multiple myeloma patients: Serum CCL3, TRACP-5b and Sclerostin in multiple myeloma patients - Jiang, Cuimei; Sun, ManMan; Gao, Dashan; Zhang, Xiaoli; Pan, Jianan (Journal of Medical Biochemistry, 2025)
[Objective] To investigate the clinical use of Sclerostin, tartrate-resistant acid phosphatase 5b (TRACP-5b), and serum C-C motif chemokine ligand 3 (CCL3) levels in assessing the health and prognosis of patients with multiple myeloma. [Methods] 250 patients with multiple myeloma who visited the hospital between January 2023 and December 2024 were selected as the observation group, whereas 150 healthy individuals who were evaluated there during that time made up the control group. The levels of serum CCL3, TRACP-5b and Sclerostin in the observation group before and after treatment were compared, as were the levels of serum CCL3, TRACP-5b and Sclerostin. The levels of serum CCL3, TRACP-5b and Sclerostin in MM patients with different tumor stages and different degrees of bone destruction were compared, and the univariate and multivariate factors of death within one year in MM patients were analyzed. To compare the predictive efficacy of single and combined detection of serum CCL3, TRACP-5b and Sclerostin for death within one year in patients with multiple myeloma. [Results] The levels of serum CCL3, TRACP-5b and Sclerostin in the observation group before and after treatment were significantly greater than those in the control group, and the differences were statistically significant (P<0.05). After treatment, the levels of serum CCL3, TRACP-5b and Sclerostin in the observation group were significantly lower than those before treatment, and the differences were statistically significant (P<0.05). There were statistically significant differences in tumor stage, classification of degree of bone destruction, CCL3 level, TRACP-5b level and Sclerostin level (P<0.05). Multivariate analysis revealed that tumor stage, the degree of bone destruction, the CCL3level, the TRACP-5b level and the Sclerostin level were the factors influencing death within one year in patients with multiple myeloma (P<0.05). The levels of serum CCL3, TRACP-5b and Sclerostin have relatively high predictive efficacy for death within one year in patients with multiple myeloma. The sensitivity of the combined detection of the three indicators was 90.3%, the specificity was 87.4%, and the area under the receiver operating characteristic curve (AUC) was 0.937, which was significantly greater than that of CCL3 (Z=3.061, P=0.002), TRACP-5b (Z=3.625, P<0.001), and Sclerostin (Z=2.579). When tested separately (P =0.010), there was no statistically significant difference in the AUC among the three indicators (P>0.05). [Conclusion] CCL3, TRACP-5b and Sclerostin are involved in the occurrence and development of multiple myeloma and have high value in predicting death within one year.